Petrogenesis of subvolcanic rocks from the Khunik prospecting area, south of Birjand, Iran: Geochemical, Sr–Nd isotopic and U–Pb zircon constraints. (1st January 2016) - Samiee, Somayeh; Karimpour, Mohammad Hassan; Ghaderi, Majid; Haidarian Shahri, Mohammad Reza; Klöetzli, Urs; Santos, José Francisco
Highlights: Subvolcanic rocks of the Khunik area that are related to mineralization, were formed in early Oligocene (38 ± 1 Ma). This subvolcanic rocks have features typical of I-type granitoids and belong to magnetite series. Magmas of Khunik area formed in volcanic arc setting related to subduction of the oceanic crust under Lut block plate. Abstract: The Khunik prospecting area is located 106 km south of Birjand in eastern Iran, and is considered as an epithermal gold prospecting area. The mineralization is related to subvolcanic rocks. There are several outcrops of subvolcanic intrusions in the area which intruded into Paleocene–Eocene volcanic rocks (andesite, trachy-andesite and pyroclastic rocks). Petrographic studies indicate that subvolcanic rocks consist mainly of diorite, monzonite, quartz-monzonite, monzodiorite and quartz-monzodiorite. Mineralogically, these rocks contain plagioclase, K-feldspar, amphibole, pyroxene, biotite and quartz. Geochemically, they have features typical of high-K calk-alkaline to shoshonitic and are metaluminous, and also belong to magnetite granitoid series (I-type). Primitive mantle normalized trace element spider diagrams display enrichment in LILE, such as Rb, Ba, and Cs, compared to HFSE. Chondrite-normalized REE plots show moderately LREE enriched patterns (7.45 < La N /Yb N < 10.54), and no significant Eu anomalies. Tectonic discrimination diagrams also show affinities with modern convergent margin magmas, suggesting that magmas of Khunik area formed in volcanic arc setting related to subduction of the oceanic crust under the Lut Block plate. The initial 87 Sr/ 86 Sr ratios (0.704196–0.704772) and εNdi values (+1.3 to +3.3) are compatible with an origin of the parental melts in a supra-subduction mantle wedge. Zircon U–Pb dating by LA-ICP-MS indicates the age of 38 ± 1 Ma (late Eocene) for subvolcanic units that are related to mineralization. A biotite granodiorite porphyry is the testimony of the youngest magmatic activity in the area, with an age of 31 ± 1 Ma (early Oligocene). The represented dates are interpreted as magmatic crystallization ages of subvolcanic intrusions.